2019
DOI: 10.3892/etm.2019.7312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrahepatic cholestasis of pregnancy on hepatic function, changes of inflammatory cytokines and fetal outcomes

Abstract: The effects of intrahepatic cholestasis of pregnancy (ICP) on hepatic function, changes of inflammatory cytokines and fetal outcomes were studied. In total, 663 pregnant women admitted to Daqing Longnan Hospital from July 2016 to December 2017 were selected. There were, 40 cases with ICP enrolled in the observation group, and 40 normal pregnant women were recruited in the normal group. They were also grouped according to hepatic function and inflammatory cytokines, with 40 cases in each group. Neonatal Apgar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The maternal placental villi exhibit a dependent contraction response in the presence of elevated bile acid levels, resulting in acute ischemia and hypoxic symptoms. Excess CG in the blood also influences the cellular oxidative phosphorylation process, resulting in a reduction in the efficiency of fetal ATP application and, as a result, a higher risk of poor fetal outcome [ 23 , 24 ]. The findings of this paper's grouping and intergroup comparisons based on CG and TBA levels support this hypothesis, indicating that more fantastic CG and TBA levels are linked to a higher risk of poor newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The maternal placental villi exhibit a dependent contraction response in the presence of elevated bile acid levels, resulting in acute ischemia and hypoxic symptoms. Excess CG in the blood also influences the cellular oxidative phosphorylation process, resulting in a reduction in the efficiency of fetal ATP application and, as a result, a higher risk of poor fetal outcome [ 23 , 24 ]. The findings of this paper's grouping and intergroup comparisons based on CG and TBA levels support this hypothesis, indicating that more fantastic CG and TBA levels are linked to a higher risk of poor newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, the mother was reported to have mild cholestasis of pregnancy, a condition associated with higher values of TNFa, IL1b, and Il-6 in the sera, and lower values of IL-4 and IL-10 [ 31 , 32 ]. Although expected, these current findings are counterbalanced by downregulation of IFNγ expression, which is reported as a hallmark of the antiviral response even in SARS-CoV-2 infection [ 33 ], being higher in pregnancy cholestasis [ 31 ] and more significant in patients infected with SARS-CoV-2 [ 34 ], as suggested in other reports [ 24 , 35 ]. On the other hand, IFNγ expression, along with IFN-α and IL-2 has been shown to be lower during influenza epidemic in pregnant women, when compared with nonpregnant women [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5 During pregnancy, the liver and placenta are closely related to each other for bile acid transportation, immune activities, and metabolism. Wang et al 23 analyzed the correlations of maternal serum cholylglycine with umbilical artery systolic-to-diastolic ratio in ICP. They concluded that the maternal serum cholylglycine levels were positively correlated with umbilical artery systolic-to-diastolic ratio.…”
Section: Discussionmentioning
confidence: 99%